Abrasion Effects Between Cockle Shell Waste Particles and Perlite Particles in Teeth Cleaning - NGO, SIN LING; SANUSI, SHAHMIR HAYYAN (Research Progress in Mechanical and Manufacturing Engineering, 2022)
An abrasive agent in toothpaste is a substance that is used to clean the teeth by removing dental plaque with a toothbrush or other oral hygiene tool. Abrasive agents such as calcium carbonate (CaCO_3) can be extracted from natural resources such as limestones. However, improper collection of natural resources will cause pollution, but it will also disrupt its balance. As a result, using alternative resources such as recycling waste materials can help to solve this problem. This study aims to determine the possibilities of cockle shell wastes to act as toothpaste’s abrasive agent with ideal toothbrushing techniques in teeth cleaning. Cockle shell wastes was selected in this study due to their high calcium carbonate composition, and perlite (silica) particles was selected as to compare the performance between cockle shell wastes. Brushing tests was conducted using Reciprocating Toothbrushing Test Rig. Scratch analysis was conducted to investigate scratch factor and drag factor after the brushing test using Optical Microscope. At the same time, depth analysis was also conducted to discover the efficient toothbrushing parameters using Atomic Force Microscope (AFM). The wear rate for acrylic plates was investigated by the effect of load using the volume calculating method. Cockle shell wastes produced a similar trend compared to perlite particles. Hence, cockle shell wastes can act as an alternative abrasive agent in toothpaste for teeth cleaning purposes.